STRATEGI KOMUNIKASI IKATAN BUJANG DARA SEBAGAI DUTA WISATA DALAM MEMPROMOSIKAN PARIWISATA DI KABUPATEN KEPULAUAN MERANTI - Tri Cahyadi; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The association of Bujang Dara Meranti Islands as tourism ambassadors have a big role in helping the government to introduce and promote the tourism potential that exists in the Meranti Islands Regency to a wide audience. In carrying out his duties as a tourism ambassador, skills and expertise are needed in promoting tourism potential as well as having an attractive way of communication and appearance in order to influence the community. In this thesis the author only discusses how the association of Bujang Dara Meranti Islands communication strategy in promoting tourism. The purpose of this study was to determine how the communicator strategy, message strategy, media selection strategy, and what are the supporting and inhibiting factors for the association of Bujang Dara in Promoting Tourism in the Meranti Islands Regency.This research method uses qualitative research methods. The informants of this study consisted of 10 people namely, 1 from the Department of Youth Tourism and Sports in the Meranti Islands Regency, 5 from the association of Bujang Dara Meranti Islands, and 4 from the community to support this research. Data collection techniques consisted of interviews, observation and documentation, while data analysis techniques used interactive models by Huberman and Miles. The data validity checking technique uses an extension of participation and triangulation.Based on the results of research that the author has done, the results of research to identify the first problem are communicator strategies in promoting tourism are all members of the Meranti Archipelago Bujang Dara Association who have credibility and attractiveness. The message strategy is informative and persuasive by specifying information using #yokkemeranti as the tagline. The media used are social media and print media. Then related to the identification of the latter are supporting factors and inhibiting factors, where the supporting factors are the potential for tourism objects, the tourism office, and the role of the community, while the inhibiting factors are human resources, natural factors access to tourist sites, lack of mastery of foreign languages, and obstacles budget. Keywords : Communication Strategy, Bujang and Dara, Tourism Ambassador.